APOS theory : a framework for research and curriculum development in mathematics education - Arnon, Ilana; Cottrill, Jim; Dubinsky, Ed; Oktaç, Asuman; Roa Fuentes, Solange Dora (New York : Springer, 2014)
In spite of the fact that APOS Theory has been used extensively in numerous scholarly publications, in the design of textbooks, and in teaching practice, there is no single references that contains all the relevant information about its components, and provides guidance about its application. The goal of this book is to present the main elements of APOS theory. It should be useful for researchers who work with, or would like to learn more about, this theoretical approach, people who are interested in the way which mathematical conceptions are constructed according to this theory, Mathematics Education researchers, graduate students in Mathematics Education, and Mathematics instructors.
Keywords: PLANIFICACIÓN CURRICULAR; MATEMATICAS -- ESTUDIO Y ENSEÑANZA